Pemetaan dan Analisis Spasial Kasus Stunting di Kota Padang - Zurliliani Zurliliani; Dwi Marsiska Driptufany; Ilham Armi; Fajrin Fajrin; Dwi Arini (Jurnal Sains dan Ilmu Terapan, 2025)
Stunting remains one of the major chronic nutritional issues in Indonesia. According to the 2021 Indonesia Nutrition Status Study (SSGI), the national stunting prevalence reached 24.4%, while in West Sumatra Province it was recorded at 25.2% in 2022. Although Padang City showed a significant decrease to 3.7% based on 2023 e-PPGBM data, continuous intervention is still necessary. Various socioeconomic factors such as parental education, family income, number of children, and household size have been shown to influence the incidence of stunting. However, spatial-based approaches to analyze the distribution of stunting cases at the local level remain limited. This study aims to map and analyze the spatial pattern of stunting in Padang City using Geographic Information Systems (GIS). This method enables a geographic visualization of case distribution, supporting more targeted policy decisions. The findings of this study are expected to provide accurate spatial data to strengthen integrated and sustainable efforts in stunting prevention in urban areas.